Collaborative Problem Solving Oriented Education for Sustainable Development: Its Impact on Critical Thinking Skills and Sustainability Awareness - Priadi, Median Agus; Jalmo, Tri; Marpaung, Rini Rita T.; Dewi, Pramita Sylvia; Qonita, Salma (UIN Fatmawati Sukarno Bengkulu, 2026)
This research aims to determine the influence of the Education for Sustainable Development-oriented Collaborative Problem Solving model on Critical Thinking Skills and Sustainability awareness at MAN 1 Metro in 2024/2025 on ecosystem material. The population in this study were all class X students at MAN 1 Metro. The research sample was students in class X-1 as the experimental class and X-2 as the control class with the sampling technique being purposive sampling. This research is quantitative research with a quasi-experimental design. Data collection was obtained through pretest-posttest and sustainability awareness questionnaires. The type of data used is quantitative data in the form of students' critical thinking skills and sustainability awareness. The research results show that the n gain value obtained in the experimental class and control class is in the medium category, but the experimental class has a larger number, namely 0.70. Meanwhile, the results of sustainability awareness in the experimental class showed an average of 84.44 with a high interpretation. This indicates that teachers need to adopt a collaborative and sustainability-oriented learning approach so that science education, especially biology, can be more meaningful, contextual, and relevant to environmental issues both globally and locally. Thus, the results of this study imply the need to develop learning strategies that position students as critical problem solvers who have sustainability awareness to achieve sustainable development goals (SDGs) through education. So it can be concluded that there is an influence of the Collaborative Problem Solving model oriented towards Education for Sustainable Development in improving critical thinking skills and Sustainability Awareness students. The implications of the results of this study indicate that the application of Collaborative Problem Solving oriented towards Education for Sustainable Development can be an effective learning strategy to improve critical thinking skills while fostering sustainability awareness in students, so that it is relevant to be applied in 21st century education.